Multicenter Prospective Study for Laboratory Diagnosis of HHV8 Infection in Solid Organ Donors and Transplant Recipients and Evaluation of the Clinical Impact After Transplantation. Issue 8 (August 2017) - Chiereghin, Angela; Barozzi, Patrizia; Petrisli, Evangelia; Piccirilli, Giulia; Gabrielli, Liliana; Riva, Giovanni; Potenza, Leonardo; Cappelli, Gianni; De Ruvo, Nicola; Libri, Irene; Maggiore, Umberto; Morelli, Maria Cristina; et al.
Abstract : Background: We performed serological and molecular pretransplant screening in solid organ transplant (SOT) donors and recipients in north central Italy and a surveillance program for human herpesvirus 8 (HHV8) infection after transplant, aiming to establish an optimal management of HHV8 infection in SOT recipients. Methods: For pretransplant HHV8 screening in both donors and recipients, 6 serological (4 indirect immunofluorescent assays [IFA] and 2 enzyme-linked immunosorbent assays—both HHV8 lytic and latent antigen based) and 2 molecular assays were used. A reference standard to identify HHV8-positive patients was defined by at least 2 positive assays. All transplant patients at risk to develop HHV8-related disease underwent virological posttransplant monitoring by quantitative real-time polymerase chain reaction (PCR) assay. Results: Human herpesvirus 8 seroprevalence was 4% (10/249) in donors and 18% (93/517) in organ recipients. The best performance was obtained by 2 lytic antigen-based IFAs that showed almost perfect agreement to the reference standard (0.943 and 0.931 Cohen kappa). Human herpesvirus 8–DNA was detected in 6.8% and 2.9% of HHV8-seropositive donor samples by in-house nested PCR and quantitative real-time PCR assays, respectively. After transplant, 3 (25%) of 12 HHV8-mismatch patients (seropositive donor/seronegative recipient) developed a primary infection, one of whom developed a lethal nonmalignant illness. Two of 93 HHV8-seropositive recipients (2.1%) had viral replication in posttransplant period, one of whom developed Kaposi sarcoma. Conclusions: Serological assays, specifically lytic IFAs, were the best methodological approach to identify HHV8-infected SOT donors and recipients. A very low incidence (1.9%) of posttransplant HHV8-related disease was observed. Abstract : Despite an HHV8 seroprevalence of 4% and 18% in donors and recipients, respectively, HHV8-DNAemia in 3-6% of HHV8-seropositive donors, and primary infection after transplant in 25% of HHV8-mismatched patients, posttransplant HHV8-related disease including Kaposi's sarcoma is less than 2%. Supplemental digital content is available in the text.